"Useless Housewife Data" - Christie Kleinmann (The Journal of Public Interest Communications, 2026)
This archival case study examines the Love Canal disaster (1978–1980) through a public interest communications lens, analyzing how competing communication strategies advanced or obstructed the public interest and what those strategies reveal about effective environmental public interest communications practice. Applying participatory communication theory, risk communication theory, and the six spheres of influence model, the study demonstrates both the failures of corporate-controlled communication and the power of participatory, community-centered approaches, and it illustrates how those dismissed as producing “useless housewife data” transformed environmental policy.